Soil carbon dynamics in corn-based agroecosystems: results from carbon-13 natural abundance - Paul, Eldor A., author; Huggins, D. R., author; Dick, W. A., author; Christenson, D. R., author; Bundy, L. G., author; Blevins, R. L., author; Collins, H. P., author; Soil Science Society of America, publisher (Colorado State University. Libraries, 1999)
We used natural 13C abundance in soils to calculate the fate of C4-C inputs in fields cropped to continuous corn (Zea mays L.). Soil samples were collected from eight cultivated and six adjacent, noncultivated sites of the Corn Belt region of the central USA. The amount of organic C in cultivated soils declined an average of 68%, compared with adjacent, noncultivated sites. The δ 13C of cultivated soil profiles that had been under continuous corn for 8 to 35 year increased in all depth increments above that of the noncultivated profiles. The percentage of soil organic C (SOC) derived from corn residues and roots ranged from 22 to 40% of the total C. The proportion of corn-derived C, as determined by this technique, decreased with soil depth and was minimal in the 50- to 100-cm depth increments of fine-textured soils. The mean residence time of the non-corn C (C3) ranged from 36 to 108 year at the surface, and up to 769 year at the subsoil depth. The longer turnover times were associated with soils high in clay. Prairie-derived soils have a higher potential to sequester C than those derived from forests. The significant loss of total C at all sites and the slow turnover times of the incorporated C lead us to conclude that there is a substantial potential for soils to serve as a C sink and as a significant nutrient reserve in sustainable agriculture.
Keywords: ecosystem processes; soc; soil organic carbon